High Chemoselectivity in the Construction of Aryl Methyl Sulfones via an Unexpected C–S Bond Formation between Sulfonylhydrazides and Dimethyl Phosphite - Liu, Teng; Yu, Shiwen; Shen, Xiang; Li, Yixian; Liu, Jianjun; Huang, Chao; Cheng, Feixiang (Synthesis, 2021)
A highly chemoselective route to aryl methyl sulfones via an unexpected C–S bond formation between sulfonylhydrazides and dimethyl phosphite catalyzed by NaI under mild conditions has been established. This transformation provides an alternative and metal-free pathway to acquire various aryl methyl sulfones in good to excellent yields. Notably, dimethyl phosphite was employed as a stable and readily available alkyl source.
Keywords: C–S bond formation; dialkyl phosphites; aryl methyl sulfones